Perfection of Shariah Share in the progressiveness of the Halal Value Chain - Mufilh Adi Laksono (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
slamic capital market is one part of the capital market in Indonesia, stock prices are always fluctuating as well as commodities sold in the goods market according to the law of supply and demand. This research is descriptive qualitative discusses how the perfection of Islamic stocks on the development of the Islamic economy through strengthening the halal value chain in all of industries. Halal value chain is an economic sector that plays a role in economic progress. Considering the huge potential of Indonesia’s sharia economy, making Indonesia a consumer of halal products in the international market.